Analysis of prescriptions at a Family Clinic in the Federal District (Research, Society and Development, 2020)
In primary care, individual and collective actions are developed, aimed at the prevention, promotion, recovery, rehabilitation and cure of diseases. Thus, it is essential to know the pattern of medication consumption by the population, both to support planning actions in favor of access to medications, and to favor the qualification of services related to these therapeutic resources. In this context, the objective of this study was to analyze the prescriptions of drugs dispensed in a Family Clinic in the Federal District, Brazil. This is an observational, descriptive, cross-sectional, retrospective study, where the collection of secondary data from prescriptions filed at the local pharmacy was processed. 3,498 recipes were analyzed, of which 1,463 were considered valid. Within the group of valid prescriptions, 9,693 medications were identified, with an average of 2.8 ± 1.8 medications per prescription. Evaluating the recipes according to some indicators of rational use of drugs suggested by the World Health Organization, such as the percentage of antimicrobial drugs prescribed and the percentage of injectable drugs found in the prescriptions, both parameters were within what is recommended. However, the indicators of the average number of active ingredients per prescription, drugs prescribed by the Brazilian Common Denomination and the drugs present in the List of Essential Medicines in the Federal District were out of the recommendations. This study made it possible to trace the profile of medication prescription for the population served in the referred unit, contributing to the production of academic knowledge related to the topic, as well as to the collection of data that can assist local pharmaceutical management.